2011
DOI: 10.1002/job.766
|View full text |Cite
|
Sign up to set email alerts
|

A moderated mediation test of personality, coping, and health among deployed soldiers

Abstract: SummaryOur study examines how personality and coping influence soldiers' psychological health among 648 US Army personnel who were at that time deployed in Iraq at the height of an insurgency. Conscientiousness, neuroticism, and extraversion were associated with different coping behaviors, and these were in turn related to psychological distress. Conscientiousness was positively associated with problem-focused coping and negatively with avoidance coping, whereas neuroticism was most positively associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 84 publications
(132 reference statements)
0
11
0
Order By: Relevance
“…Hypothesis 6, which predicted that the positive relationship between perceived employability and work–life balance would be stronger for individuals with a strong whole‐life perspective, was also supported ( β = .22, p < .01). Given discrepancies in interaction methodologies within the SEM literature, we followed previous researchers (DiRenzo, Weer, & Linnehan, ; Peng, Riolli, Schaubroeck, & Spain, ) and ran supplementary analyses of the moderating effects using hierarchical regression. These tests complement the SEM analysis, and the findings were consistent across analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Hypothesis 6, which predicted that the positive relationship between perceived employability and work–life balance would be stronger for individuals with a strong whole‐life perspective, was also supported ( β = .22, p < .01). Given discrepancies in interaction methodologies within the SEM literature, we followed previous researchers (DiRenzo, Weer, & Linnehan, ; Peng, Riolli, Schaubroeck, & Spain, ) and ran supplementary analyses of the moderating effects using hierarchical regression. These tests complement the SEM analysis, and the findings were consistent across analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, organizations might seek to help employees develop specific coping styles, raise awareness of the benefits of using the more adaptive coping styles for work–family outcomes, and encourage employees to adopt these coping styles as part of their behavioral routines. For example, Peng, Riolli, Schaubroeck, and Spain () suggested that one organizational intervention to promote the use of problem coping is to have employees identify problematic situations over which they have control and plan ways to resolve those situations actively. Individuals may also reduce their tendency to use avoidance coping by engaging in positive self‐talk, which means replacing negative statements about the self (“I wish I could just disappear so that this problem won't bother me anymore”) with more positive and functional statements (“I can take steps to deal with this problem,” Cheng & McCarthy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest that temperament traits can play a significant role in responses to trauma both in emergency-services professionals as well as in soldiers. Most indicate that neuroticism and negative emotionality intensify symptoms of trauma [8][9][10], and extroversion and sensation seeking are buffers for its development [11][12][13][14]. The Regulative Theory of Temperament (RTT) [15] also emphasizes the role of temperament in human responses to stressful situations.…”
Section: Participantsmentioning
confidence: 99%